Practical IDL programming : creating effective data analysis and visualization applications - Gumley, Liam E. (Liam Edward) (Morgan Kaufmann, 2002)
Increasingly, scientists and engineers must quickly and efficiently analyze and visualize extremely large sets of data. Interactive Data Language, IDL, was designed to address just this need. A popular data analysis and visualization programming environment, IDL is used worldwide by scientists and engineers in fields as diverse as the physical sciences, medical physics, and engineering test and analysis. In Practical IDL Programming, Liam E. Gumley provides a solid foundation in the fundamentals of procedural programming in IDL. He presents concise information on how to develop IDL programmers that are well structured, reliable, and efficient. The example programs in the book demonstrate key concepts and provide functionality that can be applied immediately. In addition, the book offers readers practical tips and advice on IDL programming, which they would otherwise discover only after years of experience. While only modest prior programming experience is assumed, readers with experience in any procedural language will quickly translate their skills to IDL, learning the best programming practices for this new environment. Scientists, engineers, and students in educational, government, and commercial research and development environments will all appreciate the author's guidance in helping them effectively analyze and visualize data. * Presents a comprehensive and detailed treatment of IDL data types, operators, expressions, array operations, input and output, direct graphics, plotting and imaging, publication quality output, and graphical user interfaces. * Designed for novices and experienced IDL users and programmers alike. * Provides an accompanying Web site with downloadable versions of all IDL programs in the book and a link to downloadable demonstration versions of the IDL software.